Medical services general history - Macpherson, W. G. (Uckfield, East Sussex)
1. c. (xv, 463 s., [5] y. grafik, [6] s., [12] y. resim, [7] y. harita, [5] y. şema) 2. c. (viii, [3], 510 s., [23] y. harita, [3] y. plan, [2] y. şema, [5] y. grafik) 3. c. (viii, 556 s., [33] y. harita, [4] y. tablo, [5] y. grafik) 4. c. (xvi, 711 s., [9] y. harita, [1] y. resim, [2] y. plan, [2] y. şema, [3] y. grafik)